2017
DOI: 10.1111/hex.12569
|View full text |Cite
|
Sign up to set email alerts
|

Development and validation of a Chinese medication literacy measure

Abstract: BackgroundDespite the impact of medication literacy (ML) on patients’ safe use of medications, existing instruments are mostly for general health literacy measurement or designed for specific disease populations, with few specifically designed for ML.ObjectiveTo develop and validate the first Chinese medication literacy measure (ChMLM).MethodsThe ChMLM was developed by a multidisciplinary and bilingual expert panel and subsequently pilot‐tested. The final version had 17 questions in four sections: vocabulary, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
36
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(37 citation statements)
references
References 37 publications
0
36
1
Order By: Relevance
“…Medication literacy is the manifestation of health literacy in the context of medication use, and inappropriate medication use was identified to be significantly associated with low medication literacy level (Kripalani et al, 2008;Zheng et al, 2017;Lee et al, 2017). Although medication literacy is assumed to be related to health literacy, medication literacy needs more skills to practice (Sauceda et al, 2012;Pouliot et al, 2017;Yeh et al, 2017). Some studies have shown that health literacy has an insignificant and weakly positive association with self-reported medication adherence (Zhang et al, 2014;Sawkin et al, 2015;Park et al, 2018), but the findings in our study suggested that medication literacy has a significant association with adherence to medication.…”
Section: Discussionmentioning
confidence: 99%
“…Medication literacy is the manifestation of health literacy in the context of medication use, and inappropriate medication use was identified to be significantly associated with low medication literacy level (Kripalani et al, 2008;Zheng et al, 2017;Lee et al, 2017). Although medication literacy is assumed to be related to health literacy, medication literacy needs more skills to practice (Sauceda et al, 2012;Pouliot et al, 2017;Yeh et al, 2017). Some studies have shown that health literacy has an insignificant and weakly positive association with self-reported medication adherence (Zhang et al, 2014;Sawkin et al, 2015;Park et al, 2018), but the findings in our study suggested that medication literacy has a significant association with adherence to medication.…”
Section: Discussionmentioning
confidence: 99%
“…Approximately 50% of CVD patients have poor adherence to their prescribed medications, which has adverse effects on morbidity, mortality, and recurrent cardiac complications, as well as higher costs [16,17]. Many studies have shown that self-medication of antihypertensive drugs is poor in patients with hypertension, including poor adherence to antihypertensive drugs and medication errors [18]. Therefore, patients' long-term regular use of antihypertensive drugs is an important way to stabilize blood pressure, control the disease and prevent serious complications.…”
Section: Introductionmentioning
confidence: 99%
“…After pilot testing on 35 participants of the convenient samples, the findings of psychometric analyses were combined with the expert content evaluation to finalize the original measure ( Table 1 ) [ 44 ], and to develop an appropriate format of the 17-item Chinese Medication Literacy Measurement (ChMLM-17) layout (e.g., please see Supplementary File S1 for images of an OTC package label and Rx labels on the Rx bag and box). Table 1 describes the original item stems.…”
Section: Methodsmentioning
confidence: 99%
“…Potential participants living in the nine cities were referred to surveyors by local leaders or persons-in-charge in community centers, owners of street shops, schoolteachers, pharmacists in community pharmacies, or participants themselves. Other than the student interviewers’ friends, relatives, neighbors, and the customers/members of participating pharmacies and organizations were approached as potential participants [ 44 ]. The remaining potential participants were contacted via either postcards or referred by referees to determine their willingness to be interviewed in either their homes or in a safe, undisrupted public or private location.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation